SOME MECHANISMS OF ENDOGENOUS INTOXICATION AND ITS EVALUATION DURING THE COURSE OF RECTAL CANCER PATIENTS COMBINED THERAPY - Голотюк, В. В.; Терен, Т. І. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Pulse, 2019)
Objectives. To study the features of endogenous intoxication parameters in patients with rectal cancer under the influence of combined therapy. Material and methods. The results of 48 patients with the diagnosis of colorectal cancer T2-4N0-2M0 (CRC) examination are presented. Patients received preoperative course of distance gamma-therapy to the area of the tumor to a total focal dose of 40 Gy in the first phase of treatment. The operation was performed 5-6 weeks after neoadjuvant treatment. The syndrome of endogenous intoxication (EI) in patients was evaluated by determining the substances of low and medium molecular weight content in blood plasma, erythrocytes and urine before irradiation, on day 10 of radiotherapy, for 1-2 days before surgery and 3 days after surgery. Results. The coefficients based on the results of measurements that characterize the syndrome of EI were calculated. It was established that the overall level of EI in the combined treatment of cancer of the CRC consists of tumor-related intoxication, the effects of distance gamma-therapy and surgery. Conclusion. EI syndrome odds, which are calculated according to the storage and distribution of substances of low and medium molecular weight in blood plasma, erythrocytes and urine are informative indicators of the endotoxemia severity and can be used for differential selection of detoxification methods.